Impact of taxes and transfers on inequality in the Asia-Pacific region - Sally Torbert (Asia-Pacific Sustainable Development Journal, 2022)
Governments that aim to adjust their fiscal policies to reduce inequality can look to several analytical tools that are being produced in Asia-Pacific countries, including commitment to equity studies and public expenditure reviews. The present paper contains a review of studies for 12 Asia-Pacific countries. Consistent with previous research on the impact of fiscal policies on inequality, the findings of the review show that policies such as targeted direct transfers, education spending and tax policies that favour direct instead of indirect taxes are most effective at inequality reduction.